Design and characterisation of a phased antenna array for intact breast hyperthermia. (3rd April 2018) - Curto, Sergio; Garcia-Miquel, Aleix; Suh, Minyoung; Vidal, Neus; Lopez-Villegas, Jose M.; Prakash, Punit
Abstract: Purpose: Currently available hyperthermia technology is not well suited to treating cancer malignancies in the intact breast. This study investigates a microwave applicator incorporating multiple patch antennas, with the goal of facilitating controllable power deposition profiles for treating lesions at diverse locations within the intact breast. Materials and methods: A 3D-computational model was implemented to assess power deposition profiles with 915 MHz applicators incorporating a hemispheric groundplane and configurations of 2, 4, 8, 12, 16 and 20 antennas. Hemispheric breast models of 90 mm and 150 mm diameter were considered, where cuboid target volumes of 10 mm edge length (1 cm 3 ) and 30 mm edge length (27 cm 3 ) were positioned at the centre of the breast, and also located 15 mm from the chest wall. The average power absorption (αPA) ratio expressed as the ratio of the PA in the target volume and in the full breast was evaluated. A 4-antenna proof-of-concept array was fabricated and experimentally evaluated. Results: Computational models identified an optimal inter-antenna spacing of 22.5° along the applicator circumference. Applicators with 8 and 12 antennas excited with constant phase presented the highest αPA at centrally located and deep-seated targets, respectively. Experimental measurements with a 4-antenna proof-of-concept array illustrated the potential for electrically steering power deposition profiles by adjusting the relative phase of the signal at antenna inputs. Conclusions: Computational models and experimental results suggest that the proposed applicator may have potential for delivering conformal thermal therapy in the intact breast.